"TIDAK PANTAS MENERIMA UANG DARI JENAZAH": Kajian Teori Konsensus dan Resiprositas pada Peristiwa Kematian - Sony Kristiantoro (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2022)
The rites associated with the death ceremony are determined by the thinking behind it, which appears in the actions lived by a particular community. Actions taken can be different in the same event. This research explores the appreciation of the meaning of the death event in Tayeman hamlet, Kopeng Village, Semarang Regency, specifically regarding the act of not providing a funeral box and not wanting to receive funeral money which is a form of sympathy, support and solidarity from the mourners to the grieving family. Even the bereaved family actually entertained the mourners like a party. This interesting phenomenon is studied from the perspective of consensus and reciprocity theory. The method used is descriptive method with a qualitative approach through observation, direct involvement, interviews, and literature study. The results obtained are that the actions of the Tayeman hamlet community emerge through a shared appreciation that takes a long time, is formalized, and is agreed upon, and they still recognize that every human being must give and receive one another in the life they live. Because of that they still respect different customs when they are outside the area, and do not force their local wisdom to be carried out by other communities.